Answer: Step-by-step explanation: Let the 2 numbers be x and y From the problem we have that x * y = 600 and x + y = 59 From x + y = 59 -> x = 59 – y Plug x = 59 – y to x * y = 600 we have (59 – y) * y = 600 -> 59y – y^2 = 600 -> -y^2 + 59y – 600 = 0 -> y = [tex](59 – \sqrt{1081})/2[/tex] or [tex](59 + \sqrt{1081})/2[/tex] Then we could plug the answers in and find x because x = 59 – y Log in to Reply

Answer:Step-by-step explanation:Let the 2 numbers be x and y

From the problem we have that

x * y = 600 and x + y = 59

From x + y = 59 -> x = 59 – y

Plug x = 59 – y to x * y = 600 we have

(59 – y) * y = 600

-> 59y – y^2 = 600

-> -y^2 + 59y – 600 = 0

-> y = [tex](59 – \sqrt{1081})/2[/tex] or [tex](59 + \sqrt{1081})/2[/tex]

Then we could plug the answers in and find x because x = 59 – y